Business continuity and the pandemic threat learning from COVID-19 while preparing for the next pandemic - Clark, Robert A. (IT Governance Publishing, 2022)
The book looks at case studies, reviewing how different industries have been impacted by the pandemic, with the author also reflecting on his own personal experience. It also discusses the ways the virus has affected our economy and daily routines, and the psychological impact.
Includes bibliographical references
Keywords: Business enterprises -- Security measures; Risk management; Emergency management; Epidemics; Entreprises; Sécurité; Mesures; Gestion du risque; Épidémies; risk management; epidemics; Business enterprises; Security measures